Description of Self and Emotional Quotient Students in Semarang - Dwi Heppy Rochmawati; Betie Febriana; Ainun Nur Hasanah (GLOBAL HEALTH SCIENCE GROUP, 2020)
Self-esteem is a picture of a person towards himself, an individual's assessment of himself as a response to others towards appreciation and, acceptance, respect and attention that shows that he is valuable. While emotional quotient (EQ) is the ability to motivate yourself owned by someone. The purpose of this study is to describe the self-esteem and emotional quotient (EQ) of Sultan Agung 3 Semarang Islamic High School students. This quantitative research uses descriptive analytic method with 71 samples taken by proportional random sampling and cross sectional approach. There were 54 (76.1%) respondents with low self-esteem, 19 respondents had low emotional quotient and 35 respondents had high emotional quotient. While 17 (23.9%) respondents with high self-esteem, 16 respondents had high emotional quotient and 1 respondent had low emotional quotient. Using the chi square test obtained p value = 0.019 (p <0.05) Which means there is a relationship between self-esteem and emotional quotient (EQ) in Sultan Agung 3 Semarang Islamic High School students.